ONLINE CREDIT CARD FRAUD: AN EMERGING CRIME IN THE INFORMATION TECHNOLOGY - Anita Carolina (InFestasi, 2012)
While the online retailing environment has provided businesses with an unparalleled opportunity to expand and improve their profits, it has also increased the vulnerability of businesses to online credit card fraud. This paper discusses the vulnerability of online credit card payment and the risks faced by participants in online credit card payment. As well as examining the prevalence of online credit card fraud, this paper considers strategies to reduce the risk of online credit card fraud.